Gender differences in the effect of weekly working hours on occupational injury risk in the United States working population - Wirtz, Anna; Lombardi, David A; Willetts, Joanna L; Folkard, Simon; Christiani, David C (Scandinavian Journal of Work, Environment & Health, 2012)
' ' OBJECTIVES ': 'Long working hours can lead to an accumulation in fatigue that may increase worker’s risk of injury. However, it is not known if this association is different for men and women. Our aim was, therefore, to investigate gender differences in the effect of weekly working hours on occupational injury risk. ' ' METHODS ': 'The US National Health Interview Survey is a clustered, stratified, cross-sectional sample representative of the US population, collected using in-household interviews. We pooled seven years of data (2004–2010) comprising 96 915 employed workers. Annualized injury rates per 100 workers were estimated for men and women in categories of weekly working hours (<30, 31–40, 41–50, >50 hours/week). Additionally, injury risk was predicted using weighted logistic regression models by weekly working hour categories, stratified by gender, including age, ethnicity, education, type of pay, occupation, body mass index, usual sleep duration, and psychological distress as covariates. ' ' RESULTS ': 'Of 96 915 workers, 705 (0.75%) reported an injury in the last 3 months. Injury rates were higher among men and increased with increasing working hours for both genders. However, results of the adjusted logistic regression model indicated an interactive effect of working hours and gender on injury risk [odds ratio (OR) 1.02, 95% confidence interval (95% CI) 1.00–1.03). Injury risk increased among women working 41–50 hours/week (OR 1.51, 95% CI 1.03–2.21) and >50 hours/week (OR 1.69, 95% CI 1.06–2.70) compared to 31–40 hours/week but not among men. ' ' CONCLUSIONS ': 'The findings indicate an increase in injury risk with increasing working hours among women but not men.
Keywords: epidemiology; gender; gender difference; occupational injury; occupational safety; sleep; United States; weekly working hour; woman; work hour; working population